Variations In Methods For Storing Samples From Diabetes Mellitus Patients On The Results Of Urine Leukocyte Examination - Maulidiyah , Hikmatul; Puspitasari (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Diabetes mellitus (DM) is often accompanied by both microvascular and macrovascular. One of the common complications  in patients with diabetes mellitus is a urinary tract infection. The purpose of this study was to determine the difference between using a 10% formaldehyde preservative and storage at 4°C to delay urine leukocyte examination in diabetic patients. This study employed  an  analytical observationalmethod using urine samples from patients with diabetes mellitus. A total  of six samples were obtained from Siti Fatimah Tulangan 'Aisyiyah Hospital. The research was conducted from May to June 2023. The results  indicate that there are differences in the results of urine leukocyte examinations in diabetes mellitus patients based on the variations in sample storage methods.   Keywords: Delayed, diabetes mellitus, leukocytes, storage, urine.